'I am treated well if I adhere to my HIV medication': putting patient–provider interactions in context through insights from qualitative research in five sub-Saharan African countries. (23rd July 2017) - Ondenge, Ken; Renju, Jenny; Bonnington, Oliver; Moshabela, Mosa; Wamoyi, Joyce; Nyamukapa, Constance; Seeley, Janet; Wringe, Alison; Skovdal, Morten
Abstract : Objectives: The nature of patient–provider interactions and communication is widely documented to significantly impact on patient experiences, treatment adherence and health outcomes. Yet little is known about the broader contextual factors and dynamics that shape patient–provider interactions in high HIV prevalence and limited-resource settings. Drawing on qualitative research from five sub-Saharan African countries, we seek to unpack local dynamics that serve to hinder or facilitate productive patient–provider interactions. Methods: This qualitative study, conducted in Kisumu (Kenya), Kisesa (Tanzania), Manicaland (Zimbabwe), Karonga (Malawi) and uMkhanyakude (South Africa), draws upon 278 in-depth interviews with purposively sampled people living with HIV with different diagnosis and treatment histories, 29 family members of people who died due to HIV and 38 HIV healthcare workers. Data were collected using topic guides that explored patient testing and antiretroviral therapy treatment journeys. Thematic analysis was conducted, aided by NVivo V.8.0 software. Results: Our analysis revealed an array of inter-related contextual factors and power dynamics shaping patient–provider interactions. These included (1) participants' perceptions of roles and identities of 'self' and 'other'; (2) conformity or resistance to the 'rules of HIV service engagement' and a 'patient-persona'; (3) the influence of significant others' views on service provision; and (4) resources in health services. We observed that these four factors/dynamics were located in the wider context of conceptualisations of power, autonomy and structure. Conclusion: Patient–provider interaction is complex, multidimensional and deeply embedded in wider social dynamics. Multiple contextual domains shape patient–provider interactions in the context of HIV in sub-Saharan Africa. Interventions to improve patient experiences and treatment adherence through enhanced interactions need to go beyond the existing focus on patient–provider communication strategies.